The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/s004310050006
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal development and growth after total-body irradiation and bone marrow transplantation for haematological malignancies

Abstract: Careful monitoring of both gonadal function and growth after bone marrow transplantation and total body irradiation is warranted in order to detect disturbances early and ensure normal pubertal development in children treated for haematological malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 26 publications
(25 reference statements)
7
71
1
1
Order By: Relevance
“…Patients treated with TBI at a young age, and who have many years of linear growth ahead of them, are likely to suffer a greater height-loss than those treated at an older age; younger age at the time of SCT has, indeed, invariably been cited as a major risk factor for short stature in pediatric SCT recipients. 3,6,9,[22][23][24][25][26][27][28][29] The final height data reported by seven other studies are summarized in Table 4. 9,[22][23][24][25][26][27] In contrast to the studies by Bakker et al 22,26 and Cohen et al, 9 but in keeping with the findings of others, 23,25 we did not find a significant interaction between gender and final height.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients treated with TBI at a young age, and who have many years of linear growth ahead of them, are likely to suffer a greater height-loss than those treated at an older age; younger age at the time of SCT has, indeed, invariably been cited as a major risk factor for short stature in pediatric SCT recipients. 3,6,9,[22][23][24][25][26][27][28][29] The final height data reported by seven other studies are summarized in Table 4. 9,[22][23][24][25][26][27] In contrast to the studies by Bakker et al 22,26 and Cohen et al, 9 but in keeping with the findings of others, 23,25 we did not find a significant interaction between gender and final height.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][22][23][24]27,28 Prior cranial radiotherapy has been cited as a significant risk factor for height loss in many reports of The final sitting height s.d.s. in our cohort was severely impaired, with a mean value of À2.2.…”
Section: Discussionmentioning
confidence: 99%
“…The 41 boys given BMT were more likely to have altered germ cells with increased plasma FSH (61%), than altered testosterone secretion, which is partially or completely altered with increased LH (24.4%), as shown by others. 12,16 Treatment with testosterone was indicated in only three patients. Testicular volume was lower in those given 10 Gy TBI than in those given 6 Gy TLI, both delivered as a single dose.…”
Section: Discussionmentioning
confidence: 99%
“…of the general population, and that the type of transplantation, graft-versus-host disease, growth hormone (GH) or steroid treatment did not influence final height. 2 Bakker et al 7 also reported that male gender and a young age at the time of HCT were the only factors with an independent negative effect on longitudinal growth, whereas TBI dose (5-12 Grays (Gy)), age at the onset of puberty and the need to induce puberty did not influence growth.…”
Section: Introductionmentioning
confidence: 99%